2017
DOI: 10.5812/jpr.11507
|View full text |Cite
|
Sign up to set email alerts
|

Omalizumab (Xolair) in Children with Atopic Dermatitis: A Review Article

Abstract: Context: Atopic dermatitis is a chronic skin disease in children. The prevalence of eczema is up to 30% in the world. Omalizumab (Xolair) is a monoclonal antibody that blocks the serum IgE. The aim of this study is to review the effect of Xolair in children with atopic dermatitis. Evidence Acquisition: The data was searched in PubMed, Scopus, and Embase with keywords: atopic dermatitis, eczema, children, pediatrics, Xolair, and Omalizumab. The inclusion criteria included articles related to use of Xolair in ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Other treatment options for CHS include chemotherapy, a high dosage of methylprednisolone, and IL-2 administration. Allogenic hematopoietic stem cell transplantation (HSCT) is the most successful approach before the patient enters the accelerated phase [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other treatment options for CHS include chemotherapy, a high dosage of methylprednisolone, and IL-2 administration. Allogenic hematopoietic stem cell transplantation (HSCT) is the most successful approach before the patient enters the accelerated phase [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…An SR of omalizumab reviewed eight studies involving children with moderate–severe AE 11 . However, only one study was an RCT; the rest were cohort studies, case series and case reports, and the number of participants in each study was no greater than 11.…”
Section: Omalizumabmentioning
confidence: 99%
“…An SR of omalizumab reviewed eight studies involving children with moderate-severe AE. 11 However, only one study was an RCT; the rest were cohort studies, case series and case reports, and the number of participants in each study was no greater than 11. Although the authors concluded that omalizumab 'decreases SCORAD [SCORing Atopic Dermatitis] in all of severe AE', this assertion was based on small, uncontrolled and underpowered studies.…”
Section: Omalizumabmentioning
confidence: 99%